1997
DOI: 10.1258/0956462971919994
|View full text |Cite
|
Sign up to set email alerts
|

Condom and Nonoxynol-9 use and the incidence of HIV infection in serodiscordant couples in Zambia

Abstract: We aimed to measure the effectiveness of latex condoms and of nonoxynol-9 [N-9] spermicides, in preventing HIV transmission in heterosexual serodiscordant couples in Lusaka. Each couple was examined at clinic visits scheduled at 3-month intervals for one year or more per couple, or until seroconversion or discontinuation. Couples were given condoms and their choice of 3 N-9 products and advised to use both at every intercourse. Sexual exposure was ascertained from coital logs that recorded coitus and barrier m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
59
0
2

Year Published

1999
1999
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(61 citation statements)
references
References 20 publications
0
59
0
2
Order By: Relevance
“…49 Of concern, however, were the following facts: 1) no studies ever definitively demonstrated a beneficial effect of spermicides on STD or HIV transmission with condom use; 2) spermicide use may have adverse effects (although earlier concerns about birth defects and possible urinary tract colonization have not been confirmed) 62,63 ; and 3) spermicides have been shown to cause vaginal irritation in some studies, leading to an increased risk of genital ulcers and a potentially increased risk of HIV infection. 49,64 This last concern has now been confirmed in a study performed in Africa by the Joint United Nations Program on AIDS, which found in a controlled study of more than 1000 women that those who used a condom and a spermicide with nonoxynol-9 became infected with HIV at about a 50% higher rate than those who used a condom and a placebo gel. 65 The CDC therefore issued a letter in August 2000 recommending against the use of nonoxynol-9 as a means of preventing STDs and HIV infection.…”
Section: Use Of Condoms and Other Methodsmentioning
confidence: 93%
“…49 Of concern, however, were the following facts: 1) no studies ever definitively demonstrated a beneficial effect of spermicides on STD or HIV transmission with condom use; 2) spermicide use may have adverse effects (although earlier concerns about birth defects and possible urinary tract colonization have not been confirmed) 62,63 ; and 3) spermicides have been shown to cause vaginal irritation in some studies, leading to an increased risk of genital ulcers and a potentially increased risk of HIV infection. 49,64 This last concern has now been confirmed in a study performed in Africa by the Joint United Nations Program on AIDS, which found in a controlled study of more than 1000 women that those who used a condom and a spermicide with nonoxynol-9 became infected with HIV at about a 50% higher rate than those who used a condom and a placebo gel. 65 The CDC therefore issued a letter in August 2000 recommending against the use of nonoxynol-9 as a means of preventing STDs and HIV infection.…”
Section: Use Of Condoms and Other Methodsmentioning
confidence: 93%
“…3 Could this really be the "better system" of publishing that Aronson describes 4 -a system in which the results of the global research enterprise are a commodity, owned by publishers and sold to those who can afford access, instead of being a global public good? A Wellcome Trust report concluded that the subscription based, restricted access system "does not operate in the long term interests of the research community" 5 and that it is hard to see how it is serving the public.…”
Section: Access Controls On Bmjcommentioning
confidence: 99%
“…Similarly, the majority of HIV infection in sub-Saharan Africa occurs in marital and cohabiting relationships [3][4]. Typically, condom use increases following a seropositive diagnosis or intervention, but is not sustained over 6 months [5][6][7] and couples do not protect the uninfected partner [8].…”
Section: Introductionmentioning
confidence: 99%